Improving Student's Listening Skills through Plays Audiovisual Learning Novel - Oktaviandi Bertua Pardede; Mikha Theresia Apriliani S; Asima Dormauli Simatupang; Novri A Panggabean (Randwick International of Education and Linguistics Science Journal, 2022)
This study aims to improve the listening skills of students at Cendramata Junior High School Medan by using audiovisual learning novels. The research population is class VII with a total of 15 people. The research method uses Classroom Action Research (CAR) with 2 cycles. The data analyzed qualitatively will describe the quality of students' listening skills in CAR. The study also tested the hypotheses which were analyzed using the Wilcoxon test to determine the significance of improving students' listening skills. The research concludes that students' listening skills can be optimized through audiovisual playback. It appears that 80% of students are able to synthesize the story plot in the novel. Mastery learning outcomes have also reached 86.7% in cycle 2 with an average score of 79.33. The increase in learning outcomes obtained is also significant, namely sig < that is accepted by Ha, namely there are differences in student scores between cycles. Based on the Wilcoxon test, it was known that there were 11 students in cycle 1 whose scores increased in cycle 2 and only 4 students whose scores remained constant. Thus, this study concludes that students experience an increase in listening skills through playing audiovisual learning novels.